STRATEGI MENGURANGI PRAKTEK RENTENIR DI KABUPATEN SUMEDANG - Rika Kusdinar; Eri Herlianti; Neng Dewi; Nur Upit Fitriyani; Rima Ramdiani; Srirahayu (Journal Of Regional Public Administration (JRPA), 2021)
Cooperative Strategy In Reducing Flender Practices In Sumedang District is the result of qualitative research that aims to answer questions about how the most important goals or objectives need to be achieved, what are the most important policies? important and directing or limiting activities, How the main action stages or programs will achieve the goals set within the boundaries outlined. The research method used in this research is descriptive analysis research with a case study approach to the object. The informants in this study were 4 people, namely the Head of the Cooperative Division, the Head of the Institutional and Human Resources Development Section, the Head of the Business Development section, and finally the Head of the Facilitation and Capital section. Data collection was done by using interview, observation and documentation techniques. The conclusion of this study is that the cooperative sector strategy in reducing the practice of loan sharks by optimizing the role of cooperatives by socializing the role and importance of cooperating in the community, presenting sharia cooperative programs, improving the performance and management of professional and accountable cooperatives by providing training and cultural-based entrepreneurial direction. local so that they can develop community business activities in order to reduce the practice of moneylenders. Suggestions that researchers can give are to improve the sharia cooperative program in each village to make it easier to carry out savings and loans in cooperatives, to socialize the role of cooperatives, to make policies specifically to reduce the practice of moneylenders and to increase cooperative business support.